Augmented Reality‐Based Interactive Scheme for Robot‐Assisted Percutaneous Renal Puncture Navigation - Zhuang, Yiwei; Wang, Shuyi; Xie, Hua; Qing, Wei; Li, Haoliang; Shen, Yuhan; Shen, Yichun (Computer animation and virtual worlds, 2025)
ABSTRACT In this paper, we present an Augmented Reality (AR)‐based application combined with a robotic system for percutaneous renal puncture navigation interaction and demonstrate its technical feasibility. Our system provides an intuitive interaction scheme between the surgeon and the robot without the need for traditional external input devices, and applies an image‐target‐based 3D registration scheme to transform the coordinate system between Hololens2 and the robot without using additional tracking devices. Users can visualize the abdominal puncture phantom and obtain 3D depth information of the lesion site by wearing Hololens2 and control the robot directly using buttons or gestures. To investigate the accuracy and feasibility of the proposed interaction scheme, six subjects were recruited to complete 3D registration alignment accuracy experiments, and puncture positioning accuracy experiments using ultrasound unaided navigation, AR unaided navigation and AR robotic navigation. The results showed that the average alignment error of 3D registration was 3.61 ± 1.05 mm. The average positioning errors of ultrasound freehand navigation, AR freehand navigation and AR robotic navigation were 7.67 ± 2.00 mm, 6.13 ± 1.07 mm and 5.52 ± 0.37 mm, respectively; the average puncture times were 34.86 ± 1.67 s, 22.40 ± 2.07 s, and 29.41 ± 1.37 s.